Relationship between Uniaxial Compressive Strength and Powder Factor of Marble at Selected Deposits - Olatunji, K. J.; Ajadi, I. A.; Akanbi, S. M.; Afolabi, A.; Bolanta, M. A. (Advances in Engineering and Technology: An International Journal, 2022)
The study was carried out to determine how the Powder Factors of marble in selected sites in Kwara and Oyo States, Nigeria i.e., Eleja Marble deposit, Oreke Marble deposit and Morlap Marble deposit, Igbetti are influenced by Uniaxial Compressive Strength, and tensile strength of the rocks. The Geographical co-ordinates of the sites and depth of the drilled holes were taken and recorded, the area of each of the sites were also determined using Auto CAD software. The fresh samples of marble from the sites were taken to laboratory where Schmidt value, bulk density tests, and Uniaxial Compressive Strength (UCS) were determined. The UCS for Oreke was 100 MPa, Eleja 110 MPa, while Igbetti A and B are 95 MPa and 110 MPa respectively. The Tensile Strength for Oreke was 0.01485 MPa, Eleja 0.0123MPa, while Igbetti A and B were 0.01125 MPa and 0.00705 MPa respectively. The sites were subjected to similar drilling patterns. A graph was plotted to determine the relationship between the Powder Factor and Uniaxial Compressive Strength. The relationship between Uniaxial Compressive Strength and Powder Factor was Linear with correlation of about 0.8.